Fuzzy risk priority number assessment to detect midsole product defects - Erni Krisnaningsih; Arif Budi Sulistyo; Abdul Rahim; Saleh Dwiyatno (Universitas Serang Raya, 2022)
The quality of midsole products significantly impacts the quality, durability, and comfort of the users of shoe products manufactured by ABC company. The high percentage of the average number of product defects based on product yield data for 12 months is 3.1% which exceeds the average number of product defects required by the company by 2%. There are six types of defects in the midsole: yellowing, porous, bubbles, broken, over left material and trimming. Three types of midsole product defects from six types of defects are the focus of improvement based on the Pareto concept, the name of the type of defect is yellowing. Porous and over left material with a total defect percentage of 82.9%. This study aims to evaluate flaws in the midsole production process using a method that combines failure mode and effect analysis (FMEA), fuzzy logic, and Pareto diagram analysis. FMEA is used in shoe manufacturing to identify failure modes, their causes, and their effects. In contrast, fuzzy logic methods for input factors, such as occurrence (O), severity (S), and detection (D), are used to obtain a fuzzy risk priority number (FRPN). The assessment using rule-based FRPN provides strong evidence that the proposed methodology is logically useful for prioritizing the value of the RPN.